Taxation handbook - Duncano, Danilo A. (Manila : REX Book Store, 1989)
Contents.--v.1. Review problems.-- v.2. Review answers.--v.3. Review materials.
Keywords: Auditing -- Philippines -- Examinations, questions, etc